Messi hanging laundry at the Bernabéu: The production and consumption of Internet sports memes as trash talk. (April 2020) - Kassing, Jeffrey W.
Highlights: Like Internet memes, trash talk is communal and can be both playful and divisive. Internet sport memes extend trash talk discourse to the digital sphere. Fans used ISM to practice diminution of opponents and idolization of their players. Interpreting ISM required specific knowledge of the rivalry and current matches. Abstract: Internet memes and trash talk are communal activities that can be both playful and divisive. As such, Internet sport memes provide an instrument by which fans can broaden the extent of trash talk discourse to the digital sphere. This work explored how fan communities used Internet sport memes as trash talk within the context of the rivalry matches played between Futbol Club Barcelona and Real Madrid Club de Fùtbol. A grounded theory analysis of memes generated in response to rivalry matches indicated that fans used memes to practice diminution of their rival opponents and idolization of their own players. This was achieved by leveraging current content from recent matches, accessing in-depth knowledge about those contests and the rivalry generally, and juxtapositioning images and text to humorous effect to assert a specific reality among supporters.